Evolusi, Kepegarian, dan Spiritualitas: Memahami Realitas Pandemi dan Pasca-Pandemi Berdasarkan Pemikiran Ilia Delio - Stepanus Ammai Bungaran (EPIGRAPHE: Jurnal Teologi dan Pelayanan Kristiani, 2021)
This article assesses the pandemic and post-pandemic situation from a theological lens. The Covid-19 pandemic abruptly halted the order of life. Covid-19 imposes a new lifestyle that seems to persist even after the pandemic is considered to have passed. In this regard, it is no longer possible to see the pandemic as "abnormal."  The best option for understanding the pandemic is to accept it as a new reality and respond to it accordingly, including spiritually. The word "spiritual" in this article refers to realizing the significance of Christ's presence during the pandemic and even after the pandemic. In a very dynamic and utterly uncertain world, it takes an effort to live in Christ, which is also very dynamic and emerges in and through uncertainty. This idea is constructed based on emergentism and evolution, in particular Ilia Delio's idea about The Emergent Christ, and Gordon Kaufman's ideas about serendipitous creativity. The goal is to understand Christ as a certainty as well as uncertainty and as a spiritual way of living in the pandemic and post-pandemic. By living the uncertain Christ, Christian spirituality is being invited to live a love that is embracing, unifying, and always new. This spirituality is what is needed to support pandemic and post-pandemic life.AbstrakTulisan ini merupakan sebuah upaya memahami pandemi dan pasca-pandemi dari lensa teologi. Pandemi Covid -19 tiba-tiba saja mengubah tatanan kehidupan. Covid-19 memaksakan laku hidup baru yang tampaknya akan menjadi kesehari-harian bahkan setelah pandemi ini dianggap berlalu. Dalam konteks ini, pandemi tidak mungkin lagi dilihat sebagai kondisi “abnormal.” Pilihan terbaik memahami pandemi adalah menerimanya sebagai realitas baru dan meresponnya secara wajar, termasuk secara spiritual. Kata “spiritual” dalam tulisan mengarah sebuah upaya melihat signi-fikansi kehadiran Kristus dalam pendemi bahkan pasca-pandemi. Dalam dunia yang sangat dinamis dan serba tidak pasti, dibutuhkan sebuah upaya menghidupi Kristus yang juga sangat dinamis dan muncul di dalam dan melalui ketidakpastian. Tulisan ini merupakan undangan memahami Kristus sebagai kepastian sekaligus ketidakpastian sebagai jalan spiritual menghidupi pandemi dan pasca-pandemi. Gagasan ini dikon-struksi dari perspektif kepegarian, evolusi, gagasan Delio tentang The Emergent Christ, dan gagasan Kaufman tentang Serendipitous Creativity. Dengan menghidupi Kristus yang tidak pasti, spiritualitas Kristen sesungguhnya sedang diundang meng-hidupi cinta yang merengkuh, menyatukan, dan selalu baru. Spiritualitas inilah yang dibutuhkan menghidupi pandemi dan pasca pandemi.